Restructuring companies under crisis. A real case study - SHAYB, Hezi Aviram (Annals of Spiru Haret University. Economic Series, 2017)
Nobody is planning to fail, but many companies are failing because of lack of planning.Real business experience showed during the years that crisis can be prevented, avoided or limited. If detected in time, the risks associated with the crisis can be mitigated and the effects can be diminished, with the condition that the actions required are done fast, in a sharp and accurate manner. When it comes, a crisis brings intense level of pressure and under these conditions there is no time or room for mistakes. Delays, losing focus and lack of planning will bring a company one step away from failure. The right way to deal with crisis, if required measures are not done in time, is to minimize the losses and reposition in the best way possible. Analyzing the success stories of some of the biggest and strongest companies in the world, led to an important conclusion: the majority of these companies were in the situation to face huge crises that threatened their ability to survive in certain moments on their way to success. With the right planning and by setting a proper organizational structure, the negative aspects of the crisis can be turned into benefits and opportunities for the company. The most critical challenge for management is to assess the level of exposure to risk of the company and identify the key points to focus on in order to overcome the crisis and create value. In order to set up a strong plan in dealing with crisis, a business organization needs reliable, efficient and effective tools and this is what this article is all about.